2020
DOI: 10.3892/or.2020.7719
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CBR3 antisense RNA 1 promotes the aggressive phenotypes of non‑small‑cell lung cancer by sponging microRNA‑509‑3p and competitively upregulating HDAC9 expression

Abstract: Long noncoding RNA CBR3 antisense RNA 1 (CBR3-AS1) plays significant roles in the initiation and progression of osteosarcoma. The aim of the present study was to investigate the involvement of CBR3-AS1 in the development of non-small cell lung cancer (NSCLC). Reverse transcription-quantitative PCR was performed to detect CBR3-AS1 expression in NSCLC tissues and cell lines. The impacts of CBR3-AS1 on cellular proliferation, apoptosis, migration and invasiveness in vitro , and tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Several recent studies have found that microRNAs (miRs) are involved in post-transcriptional downregulation of HDAC9. Specifically, HDAC9 has been found to be downregulated by miR-188 in bone marrow stromal cells [27], by miR-361-5p in cells associated with cardiac hypertrophy [28], by miR-936 or miR-101-3p in retinoblastoma cells [29,30], by miR-383-5p in gastric carcinoma cells [31], by miR-211-5p in bladder cancer cells [32], by miR-30d-5p in esophageal squamous cell carcinoma cells [33], by miR-509 3p in nonsmall cell lung cancer cells [34] and by miR-377 in oral squamous cell carcinoma cells [35].…”
Section: Specific Hdac9 Expression Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have found that microRNAs (miRs) are involved in post-transcriptional downregulation of HDAC9. Specifically, HDAC9 has been found to be downregulated by miR-188 in bone marrow stromal cells [27], by miR-361-5p in cells associated with cardiac hypertrophy [28], by miR-936 or miR-101-3p in retinoblastoma cells [29,30], by miR-383-5p in gastric carcinoma cells [31], by miR-211-5p in bladder cancer cells [32], by miR-30d-5p in esophageal squamous cell carcinoma cells [33], by miR-509 3p in nonsmall cell lung cancer cells [34] and by miR-377 in oral squamous cell carcinoma cells [35].…”
Section: Specific Hdac9 Expression Patternsmentioning
confidence: 99%
“…HDAC9 is a direct target of miR5093p. It is, therefore, likely that the CBR3AS1/miR5093p/ HDAC9 pathway plays an important role in the development and progression of NSCLC [34].…”
Section: Lung Cancer (Lc)mentioning
confidence: 99%
“…It was initially found to be highly expressed in prostate cancer (PCa) 30 and to interact with androgen receptor to promote PCa cell proliferation, migration and invasion, further leading to a reduced survival rate 31 . This lncRNA was also upregulated in hepatocellular carcinoma, gastric cancer, esophageal squamous cell carcinoma 32 , nonsmall cell lung cancer 33 , colon cancer 34 and glioma 35 and was associated with poor prognosis. In Xu's study 36 , CBR3-AS1 was found to be a cancer-promoting factor associated with a worse prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…2 ) [ 93 ]. Moreover, miR-509-3p inhibits proliferation and increases apoptosis by targeting HDAC9 [ 39 ]. miR-509-3p also plays a role in treatment resistance by sensitizing ovarian cancer cells to cisplatin and olaparib by targeting XIAP , HMGA2, and RAD51 (Fig.…”
Section: The Functions Of the Chrxq273 Mirna Cluster In Cancer Progrmentioning
confidence: 99%